2005
DOI: 10.1073/pnas.0506715102
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear system theory: Another look at dependence

Abstract: Based on the nonlinear system theory, we introduce previously undescribed dependence measures for stationary causal processes. Our physical and predictive dependence measures quantify the degree of dependence of outputs on inputs in physical systems. The proposed dependence measures provide a natural framework for a limit theory for stationary processes. In particular, under conditions with quite simple forms, we present limit theorems for partial sums, empirical processes, and kernel density estimates. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
475
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 477 publications
(483 citation statements)
references
References 35 publications
4
475
0
Order By: Relevance
“…In fact, in this situation, the number of coefficients λ(nA ∩ R j ) which are not 0 or 1 is asymptotically negligible compared to n In dimension d = 1, as stated in Theorem 3 of Wu [33], the result remains true under the weaker condition p = 2. It is a consequence of Corollary 3 in [11] (see also [17]).…”
Section: 4mentioning
confidence: 66%
See 2 more Smart Citations
“…In fact, in this situation, the number of coefficients λ(nA ∩ R j ) which are not 0 or 1 is asymptotically negligible compared to n In dimension d = 1, as stated in Theorem 3 of Wu [33], the result remains true under the weaker condition p = 2. It is a consequence of Corollary 3 in [11] (see also [17]).…”
Section: 4mentioning
confidence: 66%
“…The following measure of dependence has been introduced by Wu [33] (see also [34]). Let ε 0 be a copy of ε 0 independent of (ε j ) j∈Z d and define…”
Section: Measure Of Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…However, the currently available exponential inequality associated with NED is not su¢ cient for establishing sharp empirical process results and hence fails to achieve the optimal rates of convergence for general penalized sieve extremum estimators for nonlinear semi-nonparametric models. Andrews (1991b) Another useful dependence measure for strictly stationary nonlinear time series is the so-called physical and predictive dependence measure; see, e.g., Wu (2005Wu ( , 2011. Suppose that fY t g 1 t= 1 is strictly stationary and can be represented as…”
Section: Digression: Nonlinearity and Temporal Dependencementioning
confidence: 99%
“…Hannan and Deistler (1988) showed that, for linear ARMA processes and for ≤ (log n) α , α < ∞, the infinity norm ofΓ n, − Γ n is O n −1/2 √ log log n . Wu and Pourahmadi (2009) proved the consistency of (3) for the class of non-linear short-range dependent processes considered by Wu (2005), and obtained an explicit upper bound for the operator norm ofΓ n, −Γ n See Appendix A for a review of the different matrix norms. Bickel and Gel (2011) obtained the consistency of (3) under the Frobenius norm.…”
Section: Introductionmentioning
confidence: 99%